Investigation and optimal design of band gap tunability in fractal phononic crystals - Yang Shuai; Yin Jia-Hao; Zhu Xiao-Jing; Wang Kai; Zhang Shi-ke; Cao Lu; Guo Peng-Yu; Liu Yong (Acta Acustica)
This study investigates the properties of band gaps of circular core filling fractal phononic crystals (CCFFPCs), specifically focusing on the impact of different filling positions on the frequency of band gaps. The research demonstrates that core filling at the central positions significantly influences the formation and widening of low-frequency band gaps, while filling at corner edges predominantly affects mid-frequency band gaps, and filling at edge centers effectively opens and broadens high-frequency band gaps. These results reveal the relationship between filling positions and band gap tuning, providing a theoretical foundation for precise band gap control across a full frequency range. Moreover, this study is the first to systematically clarify the impact of core filling positions on band gap frequencies, expanding the design strategies for band gaps in fractal phononic crystals. Furthermore, this study employs genetic algorithm optimization to achieve the maximum band gap width at different frequencies, enhancing the practical value of fractal phononic crystals in engineering applications. This research deepens theoretical understanding and provides valuable guidance for optimizing their use in broadband acoustic control and energy harvesting applications.